Use of long bolts for beam‐to‐concrete‐filled rectangular hollow section column joints in seismic‐resistant frames. Issue 4 (November 2016) - Van Long, Hoang; Jaspart, Jean‐Pierre; Demonceau, Jean‐François
Abstract: The research into a specific type of unstiffened extended end‐plate joint used to connect I‐shaped beams to concrete‐filled rectangular hollow section columns is presented in this paper. The main idea is to use long bolts passing through the column to connect the beam end‐plates in order to… avoid intermediate connecting elements (e.g. a reversed channel) or special bolts (e.g. blind bolts), which are sometimes used in practice, and improve the resistance and stiffness of the joint when used in seismic‐resistant frames. Firstly, a test programme was performed within an RFCS European project entitled HSS‐SERF "High‐Strength Steel in Seismic‐resistant Building Frames", 2009–2013. The test programme included defining specimens subjected to significant bending moments (and shear) or shear only. Analytical models based on the component approach and aimed at predicting the joint response were then proposed; their validity is demonstrated through comparisons with the test results. Finally, the requirements of EN 1998‐1‐1 related to full‐strength resistance for the proposed joint configuration are discussed, accounting for the actual positions of plastic hinges and the possible individual over‐strength factors for each component.